PEMANFAATAN TANAMAN HERBAL UNTUK MENINGKATKAN IMUNITAS TUBUH SELAMA PANDEMI COVID-19 - Widaryanti, Rahayu; Muflih, Muflih; Hiswati, Marselina Endah (Universitas Respati Yogyakarta, 2021)
Facing a pandemic situation, efforts are needed to control and prevent COVID-19. One of the prevention efforts that can be done is to increase community resilience, through improving individual health. The body's immune system can be maintained and improved, mainly through healthy living habits, including maintaining cleanliness, good nutrition, added with the use of health supplements and herbal ingredients or traditional medicines. This activity aims to increase public insight and knowledge about the use of herbal plants to increase body immunity during the COVID-19 pandemic. The method used is a persuasive approach through education or health education and direct practice of processing herbal ingredients. This community service involves 12 housewives and health cadres. The instruments used include pre-test and post-test sheets and checklist sheets. Then, it was analyzed by using frequency distribution for demographic data and graphs for pre-test and post-test scores. The results of community service showed that mothers who had good knowledge increased from 10% to 75%, while mothers who had low knowledge decreased from 35% to 5%.